Nomenclature of Brochoneura and Cephalosphaera (Myristicaceae), with a replacement name, Neobrochoneura, and new combinations in this genus for Madagascan species previously included in Brochoneura - Figueiredo, Estrela; Smith, Gideon F. (Phytotaxa, 2020)
The genus name Brochoneura Warburg (1895a: 179; also mentioned in Warburg 1895b: 272) was published with a single species described in it, B. usambarensis Warburg (1895a: 180; also mentioned in Warburg 1895b: 272) from East Africa. Note that both Warburg (1895a) and Warburg (1895b) were published in July 1895 (Stafleu & Cowan 1976: 763). The description of Brochoneura was though clearly published by Warburg (1895a: 179). In Warburg (1895a: 179, but not in Warburg 1895b: 272), reference was also made to three unnamed Madagascan species that likely belong in Brochoneura, but without combinations having been made for them in that genus. In a subsequent publication, Warburg (1897) included these three Madagascan species in Brochoneura, as B. madagascariensis (Lamarck 1791: 163) Warburg (1897: 234), B. acuminata (Lamarck 1791: 164) Warburg (1897: 237), and B. vouri (Baillon 1885: 454) Warburg (1897: 238). Warburg (1897) also retained his earlier B. usambarensis, which dates from 1895, in Brochoneura, but indicated it with a “(?)”, as was done by Warburg (1895b: 272).